2012
DOI: 10.3109/0142159x.2012.687480
|View full text |Cite
|
Sign up to set email alerts
|

Designing simulator-based training: An approach integrating cognitive task analysis and four-component instructional design

Abstract: Most studies of simulator-based surgical skills training have focused on the acquisition of psychomotor skills, but surgical procedures are complex tasks requiring both psychomotor and cognitive skills. As skills training is modelled on expert performance consisting partly of unconscious automatic processes that experts are not always able to explicate, simulator developers should collaborate with educational experts and physicians in developing efficient and effective training programmes. This article present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Educators needed an efficient method of teaching and assessing the information and skill that was being taught. 19,20 This teaching method also needed to be delivered in a universal, reproducible, and relatively inexpensive manner in order to be adopted in a widespread manner in UME. 17 SBT became such a teaching method, since it provided a safe environment for a student to fail, practice, and learn before a patient encounter.…”
Section: Drivers On Surgical Undergraduate Medical Educationmentioning
confidence: 99%
“…Educators needed an efficient method of teaching and assessing the information and skill that was being taught. 19,20 This teaching method also needed to be delivered in a universal, reproducible, and relatively inexpensive manner in order to be adopted in a widespread manner in UME. 17 SBT became such a teaching method, since it provided a safe environment for a student to fail, practice, and learn before a patient encounter.…”
Section: Drivers On Surgical Undergraduate Medical Educationmentioning
confidence: 99%
“…Experts should be involved in the development process of a simulator so that it can meet expectations of the intended users and to develop modules required to train relevant skills needed for practice on patients. 23,30,35 The checklists that resulted from the TNA could be a useful tool to give constructive feedback in clinical practice as we have shown that the simulator does not cover training abilities for all required skills in a TURP procedure. We recommend that future studies should focus on validation of checklists and cross-correlation of these checklists with inbuild performance metrics of a simulator, to evaluate its capability to use these checklists or the simulator as an assessment tool or as a constructive feedback mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…These frameworks assume that experts are expected to perform parts of the procedure or the whole procedure automatically and thus to make movements more fluently and to make decisions more intuitively. 30,31 From the perspective of instructional design, major advantage of simulation-based training as an adjunct to clinical practice is that the trainee can practice deliberately and, most importantly, in a safe environment where errors can be made, until a certain level of automaticity is achieved for parts of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robert Bjork, former editor of Psychological Review, has published a paper in Journal of General Internal Medicine (Bell et al 2008). Jeroen van Merriënboer, another major theoretician in cognitive load theory (van Merriënboer and Sweller 2010), is now on faculty at the University of Maastricht and has contributed articles to Medical Education (Sibbald et al 2013b; van Merriënboer and Sweller 2010), Medical Teacher, (Tjiam et al 2012) and AHSE (Sibbald et al 2013a). And there are others who are crossing the divide-Wolfgang Gaissmeier and Fred Paas come to mind.…”
mentioning
confidence: 99%